Natamycin treatment reduces the quality changes of postharvest mulberry fruit during storage. Issue 8 (29th May 2019) - Wen, Ming; Lin, Xian; Yu, Yuanshan; Wu, Jijun; Xu, Yujuan; Xiao, Gengsheng
Abstract: This study investigated the effect of natamycin (NA) treatment on the quality of mulberry fruit throughout the storage at 8°C and 90% relative humidity. The results of this study showed that NA treatment reduced the decay rate of mulberry fruit, inhibited respiration, decreased malondialdehyde (MDA) content, decreased phenylalanine ammonia‐lyase (PAL) and polyphenoloxidase (PPO) activity, and maintained sucrose levels, total soluble solids (TSS), and total acids (TA) contents in the fruits throughout storage. NA treatment maintained the surface color and firmness of fruits throughout storage and suppressed the production of fructose, glucose, total phenolics, and the contents of anthocyanin. NA treatment maintained the quality of mulberry fruit throughout storage by enhancing the enzymatic activity of the reactive oxygen species (ROS) scavengers: catalase (CAT), superoxide dismutase (SOD), and peroxidase (POD) and inhibiting the production of hydrogen peroxide (H2 O2 ). Treatment of mulberries with increasing concentrations of NA could significantly inhibit the growth of fungal pathogens in mulberry fruits and improve their quality. Practical applications: The results from our previous study showed that NA was a safe preservative which could effectively inhibit the growth of molds and yeasts in mulberry fruits and improve their quality throughout the postharvest storage. Compared with other treatments for mulberry fruit, NA treatment has the advantages of low cost, simple operation, good application, and extension. The results in this study further prove that application of NA treatment has potential in the food industry to maintain the postharvest quality and extend the shelf life of mulberry fruits throughout storage.